Jus Timun (Cucumis Sativus) Menurunkan Tekanan Darah Penderita Hipertensi pada Wanita Usia Subur - Makmun, Indriyani; Amini, Aulia; Amilia, Rizkia; Siswari, Baiq Disnalia (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2025)
Hypertension is a major risk factor for deadly non-communicable diseases. Its complications can include direct or indirect damage to organs such as the heart, brain, kidneys, and peripheral arteries. Blood pressure can be lowered through pharmacological and non-pharmacological treatments. Non-pharmacological therapy, an alternative for hypertensive patients, includes consuming foods rich in potassium, calcium, and other beneficial substances, such as cucumbers. Cucumbers are low in calories, have high moisture content, and possess strong antioxidant, anti-fat, anti-diabetic, and anti-edema properties. Hypertension itself is characterized by increased pressure against the artery walls. Generally, it is diagnosed when systolic pressure exceeds 140 mmHg and diastolic pressure exceeds 90 mmHg. This study aimed to determine the effect of Cucumis sativus administration on reducing blood pressure in women of childbearing age within the Narmada Health Center's working area in West Lombok in 2024. A quasi-experimental pretest-posttest control group design was used, comparing pre- and post-intervention data between the treatment and control groups. The study population comprised all 30 women in the area over the past three months. The sample consisted of pregnant women from Monjok village, selected using total sampling. An independent samples t-test was used for data analysis. The results showed a significant effect of Cucumis sativus on reducing blood pressure in women of childbearing age (p-value 0.007 < 0.05). This study suggests that Cucumis sativus can reduce blood pressure and may be a useful non-pharmacological treatment option.